2003
DOI: 10.1034/j.1600-0560.2003.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

The sebaceous nevus as part of the Schimmelpenning–Feuerstein–Mims Syndrome – an obvious phacomatosis first documented in 1927

Abstract: The sebaceous nevus is a common nevus and can be easily diagnosed because of its typical rough fatty surface due to its amount of sebaceous glands. In some rare cases, the sebaceous nevus is part of a genetic disorder, the Schimmelpenning-Feuerstein-Mims (SFM) syndrome. If the SFM syndrome is suspected, further investigation is necessary, because multiple organ involvement is highly likely. We suggest that diagnosis of the SFM syndrome is simple, considering the special linear arrangement of sebaceous nevi in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…It was first comprehensively described by Schimmelpenning [1957] and Happle [2004], although it was first documented in 1927 [Warnke et al, 2003]. SS has been subsumed under a plethora of names: Schimmelpenning-FeuersteinMims syndrome [Feuerstein and Mims, 1962], Solomon syndrome [Solomon et al, 1968], linear sebaceous nevus syndrome [Lansky et al, 1972;Happle, 1991], organoid nevus syndrome [Barth et al, 1977], Jadassohn nevus phakomatosis [Zaremba, 1978], and organoid nevus phakomatosis [Hornstein and Knickenberg, 1974;Bouwes Bavinck and van de Kamp, 1985].…”
Section: Introductionmentioning
confidence: 98%
“…It was first comprehensively described by Schimmelpenning [1957] and Happle [2004], although it was first documented in 1927 [Warnke et al, 2003]. SS has been subsumed under a plethora of names: Schimmelpenning-FeuersteinMims syndrome [Feuerstein and Mims, 1962], Solomon syndrome [Solomon et al, 1968], linear sebaceous nevus syndrome [Lansky et al, 1972;Happle, 1991], organoid nevus syndrome [Barth et al, 1977], Jadassohn nevus phakomatosis [Zaremba, 1978], and organoid nevus phakomatosis [Hornstein and Knickenberg, 1974;Bouwes Bavinck and van de Kamp, 1985].…”
Section: Introductionmentioning
confidence: 98%
“…As discussed by Warnke et al, 1 Schimmelpenning 2 reported two cases of a linear nevus associated with epilepsy and mental retardation in 1957. Since that time, the number of reports and findings has expanded to include a broad spectrum of nevi, including linear nevus sebaceus of Jadassohn (NSJ), that are associated with neurologic, ophthalmic, skeletal, cardiovascular, and urologic defects.…”
mentioning
confidence: 95%
“…1,3-5 These syndromes have been reported under a variety of names, including LNSS, Schimmelpenning-FeufsteinMims syndrome, and Solomon syndrome. 1,3,4 Solomon and Esterly 4 reviewed an extensive series of different types of nevi associated with other internal anomalies and grouped them under the heading of epidermal nevus syndrome (ENS). LNSS, nevus comedonicus syndrome, Becker nevus syndrome, phakomatosis pigmentokeratotica, Proteus syndrome, and congenital hemidysplasia with ichthyosiform nevus and limb defects syndrome are all considered subsets of ENS.…”
mentioning
confidence: 99%
“…[89][90][91] This syndrome, known as linear sebaceous nevus syndrome, will be described at greater length later in part 2 of this section of the JAAD.…”
mentioning
confidence: 98%